Reestructuración comercial y administrativa de la Sociedad Colombiana de Avaluadores S.A.S (2018)
The Commercial and Administrative Restructuring made to the Sociedad Colombiana de Avaluadores S.A.S, was base on four studies the first was the diagnosis where external and internal environment analysis tools were applied as the were Pestal analysis, 5 forces and Self-diagnosis of the Chamber of Commerce, allowing to see the current behavior of the organization , in the second study analyzed the market in which the organization belongs through the competitive profile matrix 8´P analysis and surveys with this analyze the behavior of the organization in its market. In the third study, the administrative proposal of the work was carried out by means of tools such as the point study for the salaries after the restructuring and finally the payroll study of restructuring was carried out the financial analysis of the Project with the help of tools such as the net present value, internal rate of return and the cost Benefit where the profitability of the Project to be carried out was analyzed.